2021
DOI: 10.13075/mp.5893.01050
|View full text |Cite
|
Sign up to set email alerts
|

A study of oxidative stress and pulmonary damage after silica instillation in rats and the effect of curcumin administration

Abstract: Background: The authors' aim was to study the dynamics of oxidative stress in experimental exposure to silica dust, to evaluate the histopathological findings in the phase preceding the formation of fibrous/fibrohyaline pulmonary nodules, and to assess the effects of curcumin administration. Material and Methods: The research was performed on 48 male Wistar rats with an average weight of 320 g. Overall, 38 rats were instilled with a single dose of 0.3 ml suspension containing 30 mg of a SiO 2 /ml saline soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Eleven studies ( Xu et al, 2007 ; Chen et al, 2008 ; Zhang et al, 2011 ; Avasarala et al, 2013 ; Chen et al, 2018 ; Gouda and Bhandary, 2018 ; Shaikh et al, 2020b ; Durairaj et al, 2020 ; Shaikh and Prabhakar Bhandary, 2020 ; Shaikh et al, 2021b ; Fathimath Muneesa et al, 2022 ) which did not include primary or secondary outcome measures were excluded. In the end, there were 27 studies were included ( Punithavathi et al, 2000 ; Venkatesan, 2000 ; Punithavathi et al, 2003 ; Punithavathi et al, 2006 ; Zhou et al, 2006 ; Zhang et al, 2007 ; Zhao et al, 2008 ; Jiang et al, 2009 ; Lee et al, 2010 ; Smith et al, 2010 ; Hamdy et al, 2012 ; Cho et al, 2013 ; Tyagi et al, 2014 ; Banerjee et al, 2015 ; Li et al, 2015 ; Kar et al, 2016 ; Tyagi et al, 2016 ; Chen et al, 2017 ; Hu Y. et al, 2018 ; Chen et al, 2019 ; Gouda M. M. et al, 2020 ; Barsan et al, 2021 ; Durairaj et al, 2021 ; Hemmati et al, 2021 ; Hosseini et al, 2021 ; Miao et al, 2021 ; Kumari and Singh, 2022 ), two of them ( Smith et al, 2010 ; Miao et al, 2021 ) were included in this meta-analysis, each of which included two independent experiments, so this study included a total of 27 studies and 29 independent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies ( Xu et al, 2007 ; Chen et al, 2008 ; Zhang et al, 2011 ; Avasarala et al, 2013 ; Chen et al, 2018 ; Gouda and Bhandary, 2018 ; Shaikh et al, 2020b ; Durairaj et al, 2020 ; Shaikh and Prabhakar Bhandary, 2020 ; Shaikh et al, 2021b ; Fathimath Muneesa et al, 2022 ) which did not include primary or secondary outcome measures were excluded. In the end, there were 27 studies were included ( Punithavathi et al, 2000 ; Venkatesan, 2000 ; Punithavathi et al, 2003 ; Punithavathi et al, 2006 ; Zhou et al, 2006 ; Zhang et al, 2007 ; Zhao et al, 2008 ; Jiang et al, 2009 ; Lee et al, 2010 ; Smith et al, 2010 ; Hamdy et al, 2012 ; Cho et al, 2013 ; Tyagi et al, 2014 ; Banerjee et al, 2015 ; Li et al, 2015 ; Kar et al, 2016 ; Tyagi et al, 2016 ; Chen et al, 2017 ; Hu Y. et al, 2018 ; Chen et al, 2019 ; Gouda M. M. et al, 2020 ; Barsan et al, 2021 ; Durairaj et al, 2021 ; Hemmati et al, 2021 ; Hosseini et al, 2021 ; Miao et al, 2021 ; Kumari and Singh, 2022 ), two of them ( Smith et al, 2010 ; Miao et al, 2021 ) were included in this meta-analysis, each of which included two independent experiments, so this study included a total of 27 studies and 29 independent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The MDA effect size was pooled from a paired comparison of five studies ( Zhou et al, 2006 ; Hamdy et al, 2012 ; Tyagi et al, 2014 ; Barsan et al, 2021 ; Hosseini et al, 2021 ), and the CUR effect was significant in the random-effects model analysis (SMD = −5.63; 95% CI = −9.66 to −1.60; heterogeneity χ2 = 30.05, df = 3, p = 0.000, I 2 = 89.9%, Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Other pulmonary fibrosis models such as paraquat-, silica particles-, radiation-, aspiration material-and amiodaroneinduced models have revealed that curcumin is able to reduce the levels of TGF-β1, TNF-α, IL-6 and collagen type I, and to decrease the generation of ROS, hydroxyproline content, MDA and MPO and iNOS activity, to increase the activity of SOD, GPx and HO-1 (Thresiamma et al, 1998;Punithavathi et al, 2003;Xu et al, 2007;Guzel et al, 2009;Jiang et al, 2009;Lee et al, 2010b;Cho et al, 2013;Barsan et al, 2021).…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
“…Some exposed individuals may be more susceptible than others to develop the disease, due to the genetic polymorphism of long non-coding RNA (lncRNA)-related single nucleotide [7]. Experimental studies confirm the early onset of oxidative damage in rats and culture cell model for silicosis, progressively evolving from the inflammatory stage to fibrosis [8,9]. Cellular damage results mainly in the generation of free radicals and the release of cytokines [10].…”
Section: Introductionmentioning
confidence: 99%